Design, Simulation and Analysis of A Novel EBG Structure using Advanced Design System: Implementation and Related Issues - Uma Maheswari Y; Amudha A; Ashok Kumar L (PREPARE@u® | IEI Conferences, 2021)
Electromagnetic noise is a operational disturbances in the high frequency operational circuits. Parasitic filters are not efficient in the case of high frequency electronic circuits. In order to mitigate the noise level in such circuits, novel electromagnetic bandgap structure is designed, simulated and measured the noise level. Electronic design automation (EDA) tools help for these work and provide the designer to prevent the rework which leads to time and cost savings. It is essential to understand the capabilities of the tool. This paper gives the design and simulation procedure of the Novel L Bridge with double square embedded Electromagnetic Bandgap structure (EBG) for the frequency range 0 GHz to 10 GHz and the same structure is implemented in hardware and measured the results using R&S®ZVH Vector Network Analyzer. It is observed that the simulated and measured results are in good alignment with the result values.